Metabolizing Risk into Paralyzing Comfort: Iménez, a Colombian Demodystopia - Torres Vergel, Frak (2024)
The purpose of this research is to analyze the various thematic and discursive elements by which Luis Noriega’s novel Iménez can be considered a demodystopia. To this end, the four coordinates of the system of signification of any demodystopia are first recognized: demography, biopolitics, science fiction and dystopia, which function as synergies present in the architecture of its meaning and as spaces of hermeneutic realization. In the second part, the characterization of these components in the novel diegesis is developed: demographic phenomenon generating the plot conflict (overpopulation), totalitarianism and deviant uses of biopolitics through coercive methods of manipulation and domination (the system of privileges), novum (the Dome), loss of freedom (conditioning and predestination) and identity alienation of the protagonist (detriment of the self).